PENGARUH LA NINA DAN EL NINO TERHADAP PENYAKIT DEMAM BERDARAH DENGUE DAN MALARIA DI INDONESIA - Indriyati, Liestiana; Mahanani, Uli (Universitas Lambung Mangkurat, 2024)
The phenomena of El nino and La nina are closely related to rainfall and its impact on various fields. Rainfall is an element of weather and climate that greatly influences all aspects of life including health, especially mosquito vector-borne diseases in Indonesia such as Dengue hemorrhagic fever (DHF), malaria, chikungunya, zika, and others. In this regard, an analytical study was carried out on the effect of El nino and La nina on DHF and malaria cases in Indonesia. This paper is the result of data analysis from the study